The attractiveness of Larut Matang Mangrove Forest Reserve as a recreational site - Rosli, Nor Fazlina (2016)
Larut Matang Mangrove Forest (LMMF) is situated in Perak under jurisdiction of Department of Forestry Perak. LMMF provides lots of marine sources for the residents. There are crabs, fish, cockles and shrimps. Not only that, mangrove forest gives out lots of benefits like timber, many activities such as sight-seeing, river cruising and birding can be done there. This study is focused to measure the attractiveness of the place through quality of activities, facilities, accessibilities and also the branding of this place. The socio demographic of the respondents were researched on to find the influence in the attractiveness of LMMF. Attractiveness is something subjective. Variety of opinions was found in literature reviews to show the meaning of attractiveness from past studies. 300 respondents were asked to fill in the questionnaires in order to find out what make the mangrove attractive for them. The result shows that its location is the main attribute of factor analysis, followed by the interesting experience offered and also the facilities and interpretation. In the study, only education levels of socio demographic gave significant values for t-test with R2 = 70.9 %. While, education and number of visit to LMMF showed the significant effects of attractiveness to the respondents. The benefits of the study will directly contribute to the betterment of the management of LMMF and improving the quality of facilities that have already been provided. Besides, it will definitely allows visitors to gain great experience especially when when the management team takes action to solve the problems occurring.